2016
DOI: 10.5194/isprsarchives-xli-b3-323-2016
|View full text |Cite
|
Sign up to set email alerts
|

Multispectral Airborne Laser Scanning for Automated Map Updating

Abstract: ABSTRACT:During the last 20 years, airborne laser scanning (ALS), often combined with multispectral information from aerial images, has shown its high feasibility for automated mapping processes. Recently, the first multispectral airborne laser scanners have been launched, and multispectral information is for the first time directly available for 3D ALS point clouds. This article discusses the potential of this new single-sensor technology in map updating, especially in automated object detection and change de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…These instruments utilize a supercontinuum laser source that is powerful enough to not be eye-safe, limiting their operation in the field, with the exception of a terrestrial laser scanner operating at two wavelengths, which is also portable (Douglas et al, 2012 ). Recently, a commercial multispectral laser scanner—the Optech Titan (Teledyne Optech, Canada)—with three channels has become available for airborne measurements (Matikainen et al, 2016 ). The development of multispectral laser scanning instruments widens the possibilities of using laser scanning data as more information about the target's reflectance becomes available in a three-dimensional format.…”
Section: Introductionmentioning
confidence: 99%
“…These instruments utilize a supercontinuum laser source that is powerful enough to not be eye-safe, limiting their operation in the field, with the exception of a terrestrial laser scanner operating at two wavelengths, which is also portable (Douglas et al, 2012 ). Recently, a commercial multispectral laser scanner—the Optech Titan (Teledyne Optech, Canada)—with three channels has become available for airborne measurements (Matikainen et al, 2016 ). The development of multispectral laser scanning instruments widens the possibilities of using laser scanning data as more information about the target's reflectance becomes available in a three-dimensional format.…”
Section: Introductionmentioning
confidence: 99%
“…Teo and Shih [ 47 ] suggested a CD method, in which the change in building types were obtained by handling multi-temporal interpolated LiDAR data. Recently, Matikanen et al [ 40 , 41 ] demonstrated the potential of multispectral airborne laser in automated classification and change detection. Land cover classification was derived from multispectral ALS data using a random forest classifier.…”
Section: Related Workmentioning
confidence: 99%
“…Each wavelength has its advantages and disadvantages, depending on the target reflectance, background radiation, atmospheric transmission, and eye safety issues [1]. The first operational multispectral airborne laser scanning (ALS) system, Titan, was launched by Teledyne Optech (Ontario, Canada) in January 2015 [2]. The sensor includes three active imaging channels of different wavelengths: 532 nm (visible), 1064 nm (near-infrared, NIR), and 1550 nm (infrared, IR).…”
Section: Introductionmentioning
confidence: 99%